Reflections on the Clinician's Role with Individuals Who Self-identify as Transgender. - Levine, Stephen B. (Archives of Sexual Behavior, 2021)
The fact that modern patterns of the treatment of trans individuals are not based on controlled or long-term comprehensive follow-up studies has allowed many ethical tensions to persist. These have been intensifying as the numbers of adolescent girls declare themselves to be trans, have gender dysphoria, or are "boys." This essay aims to assist clinicians in their initial approach to trans patients of any age. Gender identity is only one aspect of an individual's multifaceted identity. The contributions to the passionate positions in the trans culture debate are discussed along with the controversy over the official, not falsifiable, position that all gender identities are inherently normal. The essay posits that it is relevant and ethical to investigate the forces that may have propelled an individual to create and announce a new identity. Some of these biological, social, and psychological forces are enumerated. Using the adolescent patient as an example, a model for a comprehensive evaluation process and its goals are provided. The essay is framed within a developmental perspective.